Effects of Preoperative Embolization on Juvenile Nasopharyngeal Angiofibroma Surgical Outcomes: A Study of the Kids' Inpatient Database - Choi, Jonathan S.; Yu, Justin; Lovin, Benjamin D.; Chapel, Alyssa C.; Patel, Akash J.; Gallagher, K. Kelly (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives The aim of the study is to evaluate the effect of preoperative vascular embolization (PVE) on juvenile nasopharyngeal angiofibroma (JNA) surgical outcomes using a national pediatric hospitalization database.Methods The health care cost and utilization project Kids' Inpatient Database was queried for all cases of operative management of JNA between the years of 1997 and 2016. Cases were stratified based on whether the patient received PVE. A multiple linear regression was used to predict the effect of PVE on hospital length of stay (LOS) and total cost while controlling for patient demographic factors and comorbidities. The odds ratio (OR) of receiving a perioperative blood transfusion was computed using a binary logistic regression for PVE patients.Results A total of 473 patients who underwent JNA surgical resection in this time period were identified. The use of PVE has increased from 0% in 1997 to 66% of all cases by 2016. PVE was found to decrease LOS by 1 day (p = 0.036) and decrease the odds of needing a perioperative blood transfusion (OR = 0.511, p = 0.041). Patients receiving PVE were charged an additional $35,600 (p < 0.001), but recent data in 2016 indicate that hospital costs for PVE are decreasing.Conclusion PVE of JNA is becoming increasingly prevalent. Embolization results in decreased hospital LOS and lower odds of needing blood transfusions. While embolization increases the cost of management, this trend should be re-evaluated as this procedure is becoming more widespread.
Keywords: JNA; embolization; length of stay; preoperative vascular embolization; health care cost